Transcending textuality : Quevedo and political authority in the age of print - García-Bryce, Ariadna, 1968- (Penn State Romance studies., 2011)
"Examines the political writings of the seventeenth-century Spanish poet Francisco de Quevedo within the context of the social and material practices of spectacle culture"--Provided by publisher.